Effect of Heat Treatment on Creep Properties of in situ Synthesized (TiB+La2O3)/Ti Composite - Li, Jiuxiao; Han, Yuanfei; Yang, Dongye; Mao, Jianwei (Frontiers in Materials, 2019)
(TiB+La2O3)/IMI834 titanium matrix composites (TMCs) were developed by in situ synthesized in a consumable vacuum arc-remelting furnace. A new TRIPLEX treatment and β heat treatment were developed in this study. The effect of heat treatment on microstructure, tensile properties and creep rupture behavior of in situ synthesized (TiB+La2O3)/IMI834 titanium matrix composites (TMCs) and corresponding matrix alloy were investigated. The results show that widmanstätten and lamellar α structure formed after the new TRIPLEX heat treatment procedures. Compared with traditional β heat treatment, the creep strain rate increases slightly, but the elongation increases significantly (increase 126% at 293K, 59.13% at 873K). The fracture mechanism is attributed to the broken of TiB whiskers after bearing high stress. The creep fracture mechanism is due to the load transfer of TiB whiskers and interfacial debonding. The Creep strain rates of TMCs are lower than that of matrix alloy, which is attribute to that loading of TiB and the pinning effect of finer La2O3 particles on dislocation movement.